Screening of powdery mildew resistant barley accessions from Ethiopia for tolerance to abiotic stressors - R. A. Abdullaev; O. V. Yakovleva; I. A. Kosareva; E. E. Radchenko; B. A. Batasheva (Труды по прикладной ботанике, генетике и селекции, 2020)
Background. Analyzing the adaptive potential of cultivated barley with the aim of using new genotypes selected and developed in the process of work is a priority trend in scientific research. The Ethiopian barleys adapted to a variety of soil and climate conditions are characterized by many valuable biological and agronomic traits. Of particular value are genotypes that combine resistance to harmful organisms and environmental stressors.Materials and methods. The collection accessions of Ethiopian barley possessing powdery mildew resistance were studied for tolerance to adverse edaphic factors (chloride salinity and high content of toxic aluminum ions in the soil). Resistance to abiotic stressors was assessed in laboratory experiments. In the study of salt tolerance, a ‘roll-based’ assessment technique was used, which takes into account the inhibition of root growth under salt (NaCl) stress conditions, compared with the reference conditions without salinization. Aluminum sensitivity of barley accessions was diagnosed in the early stages of plant development using the root test.Results and conclusions. A polymorphism of Ethiopian barleys for resistance to adverse edaphic factors was revealed. Twentyone new sources of barley resistance to toxic aluminum ions were identified, of which accessions k-8552 and k-22933 were classified as highly resistant. Accessions k-17554, k-19975, k-20029, k-20048, k-22752, k-23450 and k-25009 proved resistant to soil salinization. Barley accessions k-17554, k-22752 and k-25009 were characterized by complex resistance to powdery mildew, toxic aluminum ions, and chloride soil salinity.